Selected 19th-Century Poetic Paeans Celebrating Stanisław Moniuszko - Berkan-Jabłońska, Maria (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
This article has a nature of a record. It was inspired by the 200th anniversary of the birth of Stanisław Moniuszko, and its main goal is to reference selected celebratory poems created in the 19th century in order to commemorate the composer. The author of this article indicated how different authors interpreted the ideological expressions of Moniuszko’s music, its sources, and the functions it fulfilled. She also discussed the directions of the evolution regarding how the composer was depicted in poetry, as he was initially perceived as a “native busker”, a Vilnius lyrnik, and a compatriot, and he gradually gained the rank of a folk minstrel and a prophet able to reproduce the “lyrical genius of the nation”.